2022
DOI: 10.1007/s40123-022-00631-7
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Voice in Neovascular Age-Related Macular Degeneration: Findings from a Qualitative Study

Abstract: Introduction: Visual impairment resulting from diseases such as neovascular age-related macular degeneration (nAMD) may cause behavioural, environmental, psychological, and logistical challenges that could act as barriers to effective uptake and sustainability of treatment with anti-vascular endothelial growth factor agents (anti-VEGFs). Understanding emotions and experiences of patients with nAMD may help inform the determinants of adherence, and could contribute to improvements in ophthalmic outcomes and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Conversely, another hospital handled this issue effectively by providing advance notice of appointments, which was appreciated by patients. These findings align with the work of Talks et al , 4 who suggest that knowing and understanding the timing of intraocular injections allows patients to mentally prepare and have confidence in the treatment process. These insights of the present study may inspire changes in organisational workflows that provide patients with advance appointment information and involve them in the planning process.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Conversely, another hospital handled this issue effectively by providing advance notice of appointments, which was appreciated by patients. These findings align with the work of Talks et al , 4 who suggest that knowing and understanding the timing of intraocular injections allows patients to mentally prepare and have confidence in the treatment process. These insights of the present study may inspire changes in organisational workflows that provide patients with advance appointment information and involve them in the planning process.…”
Section: Discussionsupporting
confidence: 88%
“…11 Furthermore, a study reported scenarios where patients would consider stopping nAMD treatment, including a perceived lack of treatment effectiveness, side effects outweighing benefits, changes in reimbursement and difficulties related to transportation. 4 Although it is known that some patients with nAMD do not adhere to the recommended treatment regimen, there is limited understanding of the factors contributing to their discontinuation or omission of treatment. This is especially relevant in a country like Denmark, where treatment is tax funded, unlike in other countries where patients are more aware of the cost.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 3 more Smart Citations